Addressing post-stroke care in rural areas with Peru as a case study. Placing emphasis on evidence-based pragmatism - Miranda J.J. (2017)
Stroke is a major cause of death and disability, with most of its burden now affecting low- and middle-income countries (LMIC). People in rural areas of LMIC who have a stroke receive very little acute stroke care and local healthcare workers and family caregivers in these regions lack the necessary knowledge to assist them. Intriguingly, a recent rapid growth in cell-phone use and digital technology in rural areas has not yet been appropriately exploited for health care training and delivery purposes. What should be done in rural areas, at the community setting-level, where access to healthcare is limited remains a challenge. We review the evidence on improving post-stroke outcomes including lowering the risks of functional disability, stroke recurrence, and mortality, and propose some approaches, to target post-stroke care and rehabilitation, noting key challenges in designing suitable interventions and emphasizing the advantages mHealth and communication technologies can offer.